Lo más fresco de la Florida: Persimos - Claudia Peñuela (EDIS)
This series of 2-page illustrated fact sheets are Spanish language translations of the Florida Fresh series, about fruits and vegetables available in Florida’s farmers’ markets. They include nutrition facts, brief discussion of why consumers should buy locally, information about where and when the produce is available in Florida, selection tips, and recipes. Published by the UF Department of Family Youth and Community Sciences, August 2009.